Economic agendas old and new and Chinese administrative reform - Bennett Gordon
Facing new agenda economic development issues, China like other developing states is forced to coordinate policies regionally. As need for decentralization "down-ward" stretches to include delegation "outward", Beijing must find its best response to the new trend. Four tests reveal no reason for China to stay aloof from simple Membership in Pacific-Asian regional organizations. Three tests reveal no problem with China taking an activist role in such regional organizations. Three final tests reveal potential costs China would pay for seeking a regional leadership role, especially before Beijing's post-succession direction is determind. The old economic development agenda demands tackling poverty at the nati
Keywords: China -- Economic Policy; Economic Development -- China; Administrative Reforms -- China; Administrative Reorganisation -- China